Analysis of Self-Efficacy and User Satisfaction in Sustainable Use of The GOBIS Surabaya Application through PLS-SEM Approach - Sony Abdhillah; Tikno Tikno (Diponegoro University, 2025)
This study aims to examine the factors influencing the sustained usage of the GoBis e-government application in Surabaya, Indonesia. By investigating constructs such as Information Quality (IQ), Personal Outcome Expectation (POE), Self-Efficacy (SE), Satisfaction (SAT), Service Quality (SQ), Social Influence (SI), and Prior Experience (PE), the research utilizes Structural Equation Modeling - Partial Least Squares (SEM-PLS) to analyze user engagement and behavior. The analysis, based on a sample of 409 respondents, reveals that Information Quality, Personal Outcome Expectation, Self-Efficacy, and Satisfaction significantly impact users' intention to continue using the application. Specifically, Information Quality was identified as a crucial determinant, influencing Continuance Intention, Self-Efficacy, and Satisfaction, highlighting the importance of high-quality information in building user confidence and satisfaction. In contrast, Service Quality and Social Influence were found to have a limited effect on Continuance Intention, suggesting that these factors contribute to user satisfaction but are not primary drivers of long-term engagement. The findings emphasize the need for improving user experiences by enhancing information quality, promoting self-efficacy programs, and providing regular user-centered updates. The study concludes with recommendations for stakeholders to focus on continuous service improvements and regular user feedback evaluations to meet evolving public service standards and foster higher community engagement.